PEMBERDAYAAN MASYARAKAT KAWASAN MARITIM MELALUI OPTIMALISASI POTENSI SUMBER DAYA LOKAL DI DESA SEMARE PASURUAN - Aan Warul Ulum (LPPM Universitas Yudharta Pasuruan, 2018)
This activity generally aims to empower the community through the optimization of the local resource potential of the maritime area in Desa Semare, Kecamatan Kraton Kabupaten Pasuruan, which is carried out in collaboration involving the university through Kuliah Kerja Nyata Tematik Kemaritiman in 2018. This activity uses Participatory Rural Appraisal ( PRA) to establish a synergic relationship between unity with the community in terms of efforts to solve problems that occur in the field. During this activity, there were two programs implemented, namely priority programs and supporting programs. The priority program is a program that is considered an urgent need to be carried out in accordance with the capacity of the KKN-T Kemaritiman participant group. Support programs are carried out as an effort to socialize with the lives of the surrounding community. It is hoped that this activity can run sustainably as part of an effort to optimize local potential with the use of appropriate technology which leads to improved community welfare.